Mechanism driving stronger tropical cyclones in cooler autumn than the hottest summer - Vineet Kumar Singh; Hye-Ji Kim; Il-Ju Moon (npj Climate and Atmospheric Science)
Abstract Warmer sea surface temperatures (SSTs) increase evaporation, convection, and latent heat release in the atmosphere, which favors tropical cyclone (TC) intensification and ultimately leads to stronger storms. However, in this study, we find that the intensity of TCs in the western North Pacific, called typhoons, is on average higher in the colder autumn season than during the warmer summer season. The primary reason for this is that despite the decrease in SSTs during autumn, the deepening of the ocean mixed layer increase the TC heat potential and reduces storm-induced SST cooling. Atmospheric thermodynamic conditions also become more favorable to TC intensification in autumn than in summer due to higher heat and sensible heat fluxes in autumn resulting from the increased air-sea temperature/moist differences at the interface. Lastly, during autumn, the TC’s track shifts towards the equator as a result the TCs in this season travel over more favourable ocean condition which also contribute in the TC intensification. This finding will enhance the understanding of the mechanisms causing seasonal differences in TC intensity, which will aid in TC seasonal forecasting and risk assessment.